Examining a new functional electrical stimulation therapy with people with severe upper extremity hemiparesis and chronic stroke: A feasibility study. (November 2017) - Hebert, Deborah A; Bowen, James M; Ho, Cindy; Antunes, Irene; O'Reilly, Daria J; Bayley, Mark
Introduction: Upper extremity impairment post-stroke is common and results in decreased occupational engagement. For those with chronic stroke and severe hemiparesis, few treatment options are available. MyndMove™ is a functional electrical stimulation technology programmed to stimulate up to eight muscle groups in reach and grip patterns. A pre–post, cohort, feasibility study was conducted to inform the design of a randomized controlled trial examining the effectiveness of MyndMove™ therapy. Method: Individuals enrolled had chronic severe upper extremity hemiparesis following a stroke (> 6 months) with Chedoke-McMaster Stroke Assessment Stage 1–2 (arm and hand) and a Fugl-Meyer Upper Extremity score less than 19. Treatment with Myndmove™, consisting of 20 one-hour sessions, 3–5 times per week over 4–6 weeks was provided. Results: Of 25 enrolled participants, 24 (96%) completed treatment. Fifty-eight percent (14/24) of the participants demonstrated improvement equal to or exceeding the minimal clinically important difference of five on the Fugl-Meyer Upper Extremity test. Mean change from baseline Fugl-Meyer Upper Extremity overall score was 7.1 (SD 5.0) ( p < 0.001). Mean time to complete treatment was 40 days (SD 6.0). Conclusion: MyndMove™ therapy is feasible to deliver within outpatient settings and may be a suitable function-based treatment option for severe chronic stroke upper extremity impairment.